Countering Terrorists in Southeast Asia: The Hardline Approach - Arya Sandhiyudha (Jurnal Politica, 2016)
The Global War on Terror discourse in Southeast Asian countries has been responded in various ways in order to face religious-motivated terrorism. Among those, there are hardline approaches in state level classified as military-focused, intelligence-focused, and law enforcement-focused approaches. Each has different policy backgrounds and is influenced by different actors. The analysis on each’s strength and weakness is presented in this writing by focusing on four countries, i.e Philippines, Singapore, Malaysia, and Indonesia. The result shows that military-focused approach implemented in Philippines has proven as the most risky one even though has also proven as effective to paralyses terrorist group capability. Meanwhile, the use of excessive power undermines many achievement of intelligence-focused approach in Singapore and Malaysia. In both countries, neutralizing the terrorist groups is achieved by using less firepower, then decreasing the support and legitimacy of the groups in wider society. In Indonesia herself, law enforcement-focused approach has proven gaining success even though the terrorism threats remain.